2005
DOI: 10.3171/spi.2005.2.5.0624
|View full text |Cite
|
Sign up to set email alerts
|

Short-term results of microendoscopic posterior decompression for lumbar spinal stenosis

Abstract: Object. The authors applied the technique of microendoscopic discectomy to posterior decompression procedures for lumbar spinal stenosis. The purpose of this study was to determine the feasibility of using an endoscopic technique to treat lumbar spinal stenosis and to evaluate the clinical and radiographic results of microendoscopic posterior decompression (MEPD). Methods. Microend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
112
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 24 publications
6
112
0
1
Order By: Relevance
“…In line with Ikuta et al, 21 and Pao et al, 38 postoperative neural complications in form of transient dysesthesia were observed in 7.9% of patients however dysesthesia was mild and resolved gradually. The rationale of MEDL is to attempt maximal preservation the facet joint, bony anatomy, ligamentous structures and paravertebral muscles in order to maintain spinal stability; however fractures can occur to spinous process.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…In line with Ikuta et al, 21 and Pao et al, 38 postoperative neural complications in form of transient dysesthesia were observed in 7.9% of patients however dysesthesia was mild and resolved gradually. The rationale of MEDL is to attempt maximal preservation the facet joint, bony anatomy, ligamentous structures and paravertebral muscles in order to maintain spinal stability; however fractures can occur to spinous process.…”
supporting
confidence: 66%
“…In 2 similar studies, 80%, 81% patients obtained good and excellent results. 21,38 Regardless of short follow-up period in this study which precludes adequate evaluation of potential lumbar canal restenosis and long-term symptomatic deterioration as described for classic laminectomy 17 , our patients reported an overall symptomatic improvement rate of 78% for back pain, 86.3% for leg pain based on VAS scores at 3 months postoperatively. Our results are analogous to those documented by Khoo and Fessler 24 who reported a symptomatic improvement of 84%, 90% for back and leg pain respectively.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, progress has been made in minimizing the surgical approach using, for example, microscope or endoscope [5,7,14]. Another approach has been to insert an IPS to maintain segmental flexion or prevent extension, thereby indirectly decompressing nerve tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Patient disability determined with the help of Japanese Orthopaedics Association (JOA) Score All routine blood investigations required for purpose of anaesthetic fitness purpose were done in all patients. Basic Principles of Decompression Technique 6,7,8,9,10,11,12 In patient positioning: the patient is given the prone position with the lumbar region in hyperflexion. Interlaminar distance opens up so decompression can be done safely.…”
Section: Methodsmentioning
confidence: 99%